Gaps and Disparities in Chronic Hepatitis B Monitoring and Treatment in the United States, 2016-2019. Issue 4 (3rd April 2023) - Pham, Thi T. Hang; Toy, Mehlika; Hutton, David; Thompson, William; Conners, Erin E.; Nelson, Noele P.; Salomon, Joshua A.; So, Samuel
Abstract : Background: Chronic hepatitis B (CHB) carries an increased risk of death from cirrhosis and hepatocellular carcinoma (HCC). The American Association for the Study of Liver Diseases recommends patients with CHB receive monitoring of disease activity, including ALT, hepatitis B virus (HBV) DNA, hepatitis B e-antigen (HBeAg), and liver imaging for patients who experience an increased risk for HCC. HBV antiviral therapy is recommended for patients with active hepatitis and cirrhosis. Methods: Monitoring and treatment of adults with new CHB diagnoses were analyzed using Optum Clinformatics Data Mart Database claims data from January 1, 2016, to December 31, 2019. Results: Among 5978 patients with new CHB diagnosis, only 56% with cirrhosis and 50% without cirrhosis had claims for≥1 ALT and either HBV DNA or HBeAg test, and among patients recommended for HCC surveillance, 82% with cirrhosis and 57% without cirrhosis had claims for≥1 liver imaging within 12 months of diagnosis. Although antiviral treatment is recommended for patients with cirrhosis, only 29% of patients with cirrhosis had≥1 claim for HBV antiviral therapy within 12 months of CHB diagnosis. Multivariable analysis showed patients who were male, Asian, privately insured, or had cirrhosis were more likely ( P <0.05) to receive ALT and either HBV DNA or HBeAg tests and HBV antiviral therapy within 12 months of diagnosis. Conclusion: Many patients diagnosed with CHB are not receiving the clinical assessment and treatment recommended. A comprehensive initiative is needed to address the patient, provider, and system-related barriers to improve the clinical management of CHB.